Electoral legitimacy preventive representation and regularization of authoritarian democracy in Bangladesh - Moniruzzaman, Md. (IntechOpen Limited, UK, 2019)
Despite variations in its forms, contents, and qualities, arguably regular election is the only tool that upholds the “democratic” label of a government. Election works as the only legitimizing factor and, over the past several decades, it has become a popular means for authoritarian political leaders or dominant political parties in young or transitional democracies to consolidate their powerbase. Hence, elections have apparently lost their representative value and have, increasingly, been turned into a democratic means to legitimize and institutionalize undemocratic regimes. This has been the most obvious trend in Bangladesh electoral politics over the past decade. Both national and local level elections are engineered in such ways through manipulating electoral laws, the election commission, and the legal system that effectively developed an intended mechanism of preventive representation. A field of electoral competition emerged from such a mechanism where the opposition parties are formally and informally prevented from entering competition in the first place. Technically, this is shown as deliberate nonparticipation by the opposition parties but, in effect, nonparticipation is deliberately orchestrated by the ruling party. An eventual outcome is a government that is free from the parliamentary or legislative opposition, which helps to regularize an authoritarian democracy in the country.